2016
DOI: 10.1007/s12031-016-0797-5
|View full text |Cite
|
Sign up to set email alerts
|

PACAP Is Protective in a Rat Model of Retinopathy of Prematurity

Abstract: The oxygen-induced retinopathy (OIR) is a well-established rodent model of retinopathy of prematurity (ROP), which is one of the most common causes of childhood visual impairment affecting preterm babies. Pituitary adenylate cyclase-activating polypeptide (PACAP) is known to have neuroprotective effects. Several studies have revealed the presence of PACAP and its receptors in the retina and reported its protective effects in ischemic and diabetic retinopathy. In this study, we investigated whether PACAP admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…The excitotoxic damage of the retina is a main factor in retinal diseases, such as glaucoma and ischemia-induced retinopathy. We have previously shown in [ 103 ] a number of studies that PACAP is protective against excitotoxicity induced by systemic monosodium-glutamate lesion. We showed that, three times intravitreal MSG treatment on postnatal days 1, 5 and 9 caused severe neurodegeneration in the inner retinal layers in newborn rat pups [ 58 , 59 ].…”
Section: Excitotoxic Injury In the Retinamentioning
confidence: 99%
See 1 more Smart Citation
“…The excitotoxic damage of the retina is a main factor in retinal diseases, such as glaucoma and ischemia-induced retinopathy. We have previously shown in [ 103 ] a number of studies that PACAP is protective against excitotoxicity induced by systemic monosodium-glutamate lesion. We showed that, three times intravitreal MSG treatment on postnatal days 1, 5 and 9 caused severe neurodegeneration in the inner retinal layers in newborn rat pups [ 58 , 59 ].…”
Section: Excitotoxic Injury In the Retinamentioning
confidence: 99%
“…Intravitreal PACAP1-38 treatment ameliorated the vascular extent of the retinopathic eyes without alterations in vessel morphology. Moreover, cytokine expression profi les indicate that PACAP may block the new vessel formation and have a positive infl uence on the remodeling of the tissue [ 103 ].…”
Section: Retinopathy Of Prematurity (Rop)mentioning
confidence: 99%
“…In vitro, the peptide has been shown to protect whole retinal tissue cultures [20] and cell cultures from various cell types, including pigment epithelial cells [21,22] and retinal ganglion cells [23]. In vivo, PACAP is protective against NMDA-, glutamate- and kainate-induced retinal excitotoxicity [24,25,26], optic nerve transection [27], UV-induced retinal damage [28], diabetic retinopathy [29,30], retinopathy of prematurity [31] and ischemia-induced injury [32,33,34]. …”
Section: Introductionmentioning
confidence: 99%
“…It decreases the activity of matrix degrading enzymes in chondrogenic cell cultures during mechanical overload (Szentleleky et al 2019). It also has a protective function in retinopathy of prematurity (Kvarik et al 2016) and ischemic conditions (Reglodi et al 2018b). All of these facts indicate that PACAP can have important functions in fractured bone remodeling and healing.…”
Section: Discussionmentioning
confidence: 99%